Effects of subcutaneous progesterone injection as a short-time estrus synchronization protocol in ewes: a preliminary study - Behnam Valizadeh; Masoud Rajabioun; Mohammad Azizzadeh; babak Khoramian toosi (The Iranian Journal of Veterinary Science and Technology, 2022)
The present study aimed to evaluate the effect of short-time progesterone injection subcutaneously (SC) on estrus synchronization of Baluchi ewes. All ewes received one dose of PGF2α (15 mg) and then were divided into two groups. In the P4 group, a combination of progesterone and propylene glycol was subcutaneously injected twice at the three-day interval, and a vaginal sponge was used in the control group for 6 days.  On day 6, all ewes received 400 IU of eCG. 48h after eCG injection, two rams were introduced into the flock. Blood samples were taken daily from Day 0 to Day 13 to measure serum progesterone concentration. Ultrasonography was used to observe ovaries and monitor their changes at three-day intervals. In P4 and control groups, the estrus rate was 88.9% and 100% for P4 and control groups, respectively; the duration of estrus for the P4 and control groups was 8 and 8.5 days, respectively (p >0.05). No significant difference was observed in the size of the largest follicle and the number of follicles more than 2 mm in diameter between the treatment and control groups. Further studies with some changes and modifications are required for gaining acceptable fertility and prolificacy rates.